Subcomponent Self‐Assembly of a 4 nm M4L6 Tetrahedron with ZnII Vertices and Perylene Bisimide Dye Edges. Issue 7 (12th January 2015) - Frischmann, Peter D.; Kunz, Valentin; Stepanenko, Vladimir; Würthner, Frank
Abstract Formation of a tetrahedron with >4 nm perylene bisimide (PBI) dye edges and ZnII vertices in a one‐pot 22 component self‐assembly reaction is reported. The luminescent polyhedron equilibrates to a Zn2L3 helicate and disassembles upon dilution. Insights into the subcomponent self‐assembly of extended PBI ligands help to refine design rules for constructing large photofunctional metallosupramolecular hosts.